Teachers’ Evaluation of Primary English Textbooks for Vietnamese Schools Developed under the National Foreign Language 2020 Project: A Preliminary Internal Survey - Vân, Hoàng Văn (VNU Journal of Science: Education Research, 2015)
The aim of this survey research is to get evaluative feedback from the teachers who are using the primary English textbooks developed under the National Foreign Language 2020 Project to find out their strengths and weaknesses so that further corrections and revisions will be made to perfect the materials before putting them into use on a large scale . Overall, the results of the research have shown that teachers’ evaluations of the textbooks are very positive. There are, however, some things that need to be done to improve the quality of the materials. The research consists of 4 parts. Part 1 provides a brief overview of Tiếng Anh 3 and Tiếng Anh 4 - the two English textbooks which are being piloted in 92 selected primary schools throughout Vietnam. Part 2 is concerned with the design of the research which consists of aim of the research, sites and subjects of the research, research instrument, the questionnaire, research procedure, and method of data analysis. Part 3 presents in some detail research findings and discussion of those findings. Part 4 provides a résumé of the strengths and weaknesses of the textbooks as seen from the point of view of the teachers’ evaluations, points out some limitations of the research and makes some suggestions and recommendation for further study. Keywords: Teachers’ evaluation, preliminary internal survey, National Foreign Language 2020 Project, three pilot English curricula for Vietnamese schools.